Management of Complete Talocrural Luxations by Selective Talocrural Arthrodesis using Hybrid Transarticular External Skeletal Fixation in Dogs - Yardımcı, Cenk; Önyay, Taylan; İnal, Kamil S.; Özbakır, Deniz B.; Özak, Ahmet (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective This article presents a novel surgical technique in the management of open complete talocrural luxations and evaluates the results, and clinical benefits with its routine clinical utilization.Study Design Retrospective study.Animals Seventeen medium- or large-breed client-owned dogs of different breed, age and sex with complete talocrural luxations and radiographic follow-up of at least 24 weeks duration.Method Selective talocrural arthrodesis was performed by using a hybrid transarticular external skeletal fixator frame. Clinical and radiographical evaluation was performed regarding the lesion, concomitant injury, duration of the surgery, time to first use of the limb, fixator removal time, complications and clinical outcomes.Results Dogs started to use the injured limb between postoperative days 1 to 11. Pin or wire tract related complications were observed in all dogs. Time to fixator removal ranged from 57 to 90 days with a median of 73 days. All of the operated joints with an exception of one dog resulted in talocrural fusion. Mid-term clinical outcomes score was regarded as excellent in 13/17 dogs, good in 3/17 dogs and poor in 1/17 dogs subject to authors' evaluation.Conclusion A transarticular hybrid external fixator may allow early use of postoperative limb with an excellent patient compliance and is well tolerated as well. The technique showed a promising opportunity of providing favourable limb use.
Keywords: dogs; tarsal luxation; external skeletal fixation; transarticular; arthrodesis